Effects of blood sample handling procedures on measurable interleukin 6 in plasma and serum. Issue 7 (26th May 2019) - Gong, Yan; Liang, Shaocong; Zeng, Lei; Ni, Yanli; Zhou, Shaosong; Yuan, Xiaopeng
Abstract: Introduction: Interleukin‐6(IL‐6) measurement is used as a biomarker in medical diagnosis, therapy, and prognosis in various diseases. However, several pre‐analytical factors may yield a false IL‐6 result. In this study, we set out to investigate the effects of corrected blood sample handling procedures on measurable IL‐6. Method: EDTA plasma and serum samples were collected from 45 healthy individuals. The participants were divided into three groups to perform different handling procedures. Different centrifugal timing, storage temperature, and time were executed on the samples. The changed trends of IL‐6 levels were analyzed. Results: At baseline, while the paired plasma and serum IL‐6 values had a good correlation, the plasma levels were higher than serum. In general, the unseparated EDTA plasma kept steady with time. With the increase in storage temperature and time, a more pronounced rise in unseparated serum IL‐6 was observed. Nevertheless, the samples in Group 3 which centrifuged and separated immediately kept stable after a different temperature and longtime storage. Conclusion: Sample types, centrifugal timing, storage temperature, and time may affect the IL‐6 levels. A standard blood sample handling procedure should be performed to ensure the accuracy and stability of IL‐6 values.